Management of Vaginal Hyperplasia in Bitches by Bühner Suture - Roberta Bucci; Jasmine Fusi; Domenico Robbe; Maria Cristina Veronesi; Augusto Carluccio (Animals, 2022)
Vaginal hyperplasia in bitch is an exaggerated response of the vaginal mucosa to estrogens during the proestral–estral phase of the cycle that can protrude through the vulvar lips. The present study refers to the management of vaginal hyperplasia in bitches by Bühner vulvar suture. Fourteen private-owners animals were refereed for spontaneous vaginal hyperplasia and complete protrusion of the mucosa, without ischemic or necrotic areas, which occurred during the proestral–estral phase. Under general anesthesia, prolapsed mass was cleaned with 50% glucose solution to reduce oedema and gently repositioned; the Bühner suture was applied using a Gerlach needle and a sterile vaginal suture tape, maintaining a minimal opening to allow urination in order to avoid possible recurrence in the same estrus. None of the bitches showed recurrence during the current cycle, proving the effectiveness of the Bühner suture. To prevent the possible recurrence of vaginal hyperplasia at the subsequent estrus, all the bitches underwent an ovariectomy 2 months later, when the Bühner suture was removed. In conclusion, the Bühner suture proved to be useful for the conservative treatment of vaginal hyperplasia in medium- or large-sized bitches. However, this approach should be considered only for cases in which the prolapsed mass does not show trauma, ulceration, ischemic or necrotic areas.